2020
DOI: 10.3390/ijerph17239057
|View full text |Cite
|
Sign up to set email alerts
|

“RA.DI.CA.” Splint for the Management of the Mandibular Functional Limitation: A Retrospective Study on Patients with Anterior Disc Displacement without Reduction

Abstract: The study aimed at assessing the effectiveness of the RA.DI.CA. splint in the management of temporomandibular joint disc displacement without reduction (ADDwoR) and jaw functional limitation. The authors developed a retrospective clinical study. A total of 2739 medical records were screened. One hundred and forty-one patients with chronic unilateral disc displacement without reduction and jaw limitation, treated with a multifunctional RA.DI.CA. splint, were enrolled. Temporomandibular pain, headache, familiar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Several attempts have been made in the literature to recapture the anterior disc displacement without reduction,[ 2 7 8 9 10 11 ] such as mandibular manipulation to recapture the displaced disc by pulling the condyle of the affected side downward and forward. Arthroscopic disc fixation to the condylar head uses resorbable pins for internal derangement of the temporomandibular joint (stage II–IV).…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made in the literature to recapture the anterior disc displacement without reduction,[ 2 7 8 9 10 11 ] such as mandibular manipulation to recapture the displaced disc by pulling the condyle of the affected side downward and forward. Arthroscopic disc fixation to the condylar head uses resorbable pins for internal derangement of the temporomandibular joint (stage II–IV).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sousa BM et al (117) , reported an improved VAS, started at 7.1 and reached 1.4 & 0.7 in 1 month and 6 months respectively. Di Paolo et al (118) , reported VAS scores improvement from 63 to 8.32, and 70% of their patients considered themselves healed. Zhigui et al (82) , reported pain VAS of 3.89 ± 1.80, 2.23 ± 1.77, and 1.37 ± 1.57 in baseline, 3months, and 1 year respectively.…”
Section: Vas Scorementioning
confidence: 95%
“…It is generally accepted that TMDs have a multifactorial etiology and that psychosocial components, including oral behaviors and trauma, contribute to the development, exacerbation, and progression to chronic TMD [ 13 , 14 ]. However, the role of psychological factors in the development of TMD disorders is still not entirely clear [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychopathology may also discriminate between myogenous and arthrogenous groups of TMD patients [ 14 ]. According to Gatchel et al, depression is more common among individuals with chronic tension-type headaches than with TMD [ 21 ].…”
Section: Introductionmentioning
confidence: 99%